Exploratory study of the behavior of glyphosate and AMPA in three profiles of a Haplustol Entish soil province of Córdoba, Argentina - Prince, Stephania (2015)
Fil: Prince, Stephania. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.